Heart Rate and Blood Pressure Centile Curves and Distributions by Age of Hospitalized Critically Ill Children - Eytan, Danny; Goodwin, Andrew J.; Greer, Robert; Guerguerian, Anne-Marie; Laussen, Peter C. (Frontiers in Pediatrics, 2017)
Heart rate and blood pressure form the basis for monitoring the physiological state of patients. While norms have been published for healthy and hospitalized children, little is known about their distributions in critically-ill children. The objective of this study was to report the distributions of these basic physiological variables in hospitalized critically ill children. Continuous data from bedside monitors was collected and stored at five-second intervals from 3677 subjects aged 0-18 years admitted over a period of 30 months to the pediatric and cardiac intensive care units at a large quaternary children’s hospital. Approximately 1.13 billion values served to estimate age-specific distributions for these two basic physiological variables: heart rate and intra-arterial blood pressure. Centile curves were derived from the sample distributions and compared to common reference ranges. Properties such as kurtosis and skewness of these distributions are described. In comparison to previously published reference ranges, we show that children in these settings exhibit markedly higher heart rates than their healthy counterparts or children hospitalized on in-patient wards. We also compared commonly used published estimates of hypotension in children (e.g. the PALS guidelines) to the values we derived from critically-ill children. This is a first study reporting the distributions of basic physiological variables in children in the pediatric intensive care settings and the percentiles derived may serve as useful references for bedside clinicians and clinical trialscritically-ill children in this study. This is a first study reporting the distributions of basic physiological variables in children in the pediatric intensive care settings and the percentiles derived may serve as useful references for bedside clinicians and clinical trials.